Soil water storage in an upland forest after selective logging in central amazonia - Ferreira, Sávio José Filgueiras; Luizão, Flávio Jesus; Ross, Sheila M.; Biot, Y.; Mello-Ivo, W. M.P. (Revista Brasileira de Ciencia do Solo, 2004)
Soil water storage of Central Amazonian soil profiles in upland forest plots subjected to selective logging (in average, 8 trees or 34,3 m3 of timber per hectare were removed) was measured in four layers, down to a depth of 70 cm. The study lasted 27-months and was divided in two phases: measurements were carried out nearly every week during the first 15 months; in the following year, five intensive periods of measurements were performed. Five damage levels were compared: (a) control (undisturbed forest plot); (b) centre of the clearing/ gap; (c) edge of the gap; (d) edge of the remaining forest; and (e) remaining forest. The lowest values for water storage were found in the control (296 ± 19.1 mm), while the highest were observed (333 ± 25.8 mm) in the centre of the gap, during the dry period. In the older gaps (7.5-8.5 year old), soil water storage was similar to the remaining and the control forest, indicating a recovery of hydric soil properties to nearly the levels prior to selective logging.